2019
DOI: 10.3390/su11051474
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Building Design Parameters on Daylighting Metrics Using an Analysis, Prediction, and Optimization Approach Based on Statistical Learning Technique

Abstract: Daylighting metrics are used to predict the daylight availability within a building and assess the performance of a fenestration solution. In this process, building design parameters are inseparable from these metrics; therefore, we need to know which parameters are truly important and how they impact performance. The purpose of this study is to explore the relationship between building design attributes and existing daylighting metrics based on a new methodology we are proposing. This methodology involves sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…For instance, one of the SDA-metrics and the UDI-metrics must be used. A supplementary use of ASE is also important because it may seem to differ dramatically depending on the orientation [5]. A study of the new metrics for the dynamic and temporal elements of daylight has concluded that practitioners separate dynamic shades in the ASE requirement simulation methodology is a problem that not only makes it very difficult for projects to approve the scale but also nullifies the LEED Spatial Daylight Autonomy (SDA) association scale since its dynamic shades is a primary way to increase daylight while trying to control glare [6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one of the SDA-metrics and the UDI-metrics must be used. A supplementary use of ASE is also important because it may seem to differ dramatically depending on the orientation [5]. A study of the new metrics for the dynamic and temporal elements of daylight has concluded that practitioners separate dynamic shades in the ASE requirement simulation methodology is a problem that not only makes it very difficult for projects to approve the scale but also nullifies the LEED Spatial Daylight Autonomy (SDA) association scale since its dynamic shades is a primary way to increase daylight while trying to control glare [6].…”
Section: Introductionmentioning
confidence: 99%
“…Balconies produce impacts in four factors that contribute to the indoor environmental quality (thermal, visual, acoustic comfort, and indoor air quality) [13][14][15]. The light reflectance value is an important parameter when the main part of the daylight contribution comes from the internally reflected component as in the case of a deep and long balcony [16,17]. The authors of [18] developed a framework called the residential daylight score.…”
Section: Introductionmentioning
confidence: 99%
“…In the study [28], the relationship between the attributes of the building structure and the existing parameters of daylighting measuring was studied based on the new methodology. This methodology includes a statistical study.…”
Section: Introductionmentioning
confidence: 99%